Penguatan Branding Produk Olahan Ikan Lele Melalui Strategi Digital Marketing Syariah pada UMKM Desa Karangsuwung - Nakhma'ussolikhah; Ficky Adi Kurniawan (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in economic development; however, their competitiveness is often constrained by weak branding and limited digital marketing capabilities. This community engagement program aimed to strengthen brand identity and digital capacity of the “Pukle” catfish cracker MSME in Karangsuwung Village, Cirebon Regency, through an integrated branding and sharia-based digital marketing approach. A participatory–collaborative method was employed, consisting of needs assessment, Workshops, technical mentoring, and monitoring and evaluation. The interventions included the development of brand identity elements (logo, tagline, and visual guidelines), improvement of informative packaging, activation and optimization of WhatsApp Business, and utilization of TikTok Shop as a social commerce channel. In addition, a standard operating procedure for sharia-compliant digital content based on the principles of shiddiq (truthfulness), amanah (trustworthiness), fathanah (competence), and tabligh (communicativeness) was formulated to enhance consumer trust. The results indicate improvements in product professionalism, digital channel management, content consistency, and customer interaction. The integration of branding and sharia digital marketing proved relevant in building differentiation, expanding market access, and strengthening long-term business reputation. The program highlights that MSME digital transformation requires capacity building, continuous mentoring, and ethical value integration to ensure sustainable competitiveness.